Respuesta :

Answer:

Both sides were divided by 1/2.

Step-by-step explanation:

To further simplify the equation, both sides were divided by 1/2.

5x = 1/2[10 + (8x - 2)]

10x = 10 + 8x - 2

As you can see, 5x / 1/2 = 10x and 1/2[10 + (8x - 2)] = 10 + 8x - 2.

Instead of using (1/2 / 1/2)[10 + (8x - 2)] we can say 10 + 8x - 2 since 1/2 / 1/2 = 1.

Answer:

Step-by-step explanation:

At step 2:. XY = 5

Step 4. :. XY =½(RA +TP)

5x changed to 10x because 5x

were multiplied by 2 in step 5.

PLEASE MARK BRAINLIEST.